Androgen production in pediatric adrenocortical tumors may occur via both the classic and/or the alternative backdoor pathway. (5th September 2017) - Marti, Nesa; Malikova, Jana; Galván, José A.; Aebischer, Maude; Janner, Marco; Sumnik, Zdenek; Obermannova, Barbora; Escher, Genevieve; Perren, Aurel; Flück, Christa E.
Abstract: Children with adrenocortical tumors (ACTs) often present with virilization due to high tumoral androgen production, with dihydrotestosterone (DHT) as most potent androgen. Recent work revealed two pathways for DHT biosynthesis, the classic and the backdoor pathway. Usage of alternate routes for DHT production has been reported in castration-resistant prostate cancer, CAH and PCOS. To assess whether the backdoor pathway may contribute to the virilization of pediatric ACTs, we investigated seven children suffering from androgen producing tumors using steroid profiling and immunohistochemical expression studies. All cases produced large amounts of androgens of the classic and/or backdoor pathway. Variable expression of steroid enzymes was observed in carcinomas and adenomas. We found no discriminative pattern. This suggests that enhanced androgen production in pediatric ACTs is the result of deregulated steroidogenesis through multiple steroid pathways. Thus future treatments of ACTs targeting androgen overproduction should consider these novel steroid production pathways. Graphical abstract: Highlights: Pediatric adrenocortical tumors (pACT) typically produce large amounts of androgens. Androgen production in pACT may occur through the classic and/or backdoor pathway. Both adenomas and carcinomas may use the backdoor androgen production pathway. Alternate pathways may offer novel treatment targets for androgen excess disorders.